“War of Peoples for World-Views”: Werner Sombart and Ideas of 1914 - Antolović, Mihael (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2019)
One of the leading German economists and sociologists, Werner Sombart, actively took part in the "spiritual war", led by German intellectuals during World War One. Sombart systematized his views on the war that Germany led against the coalition of the enemy force in the book "Merchants and Heroes: Patriotic Rumifications" (Händler und Helden in German), published in 1915. Beside his unhidden propaganda intentions, Zombart in his book exposed the critique of the contemporary capitalist society, starting from his early anti-capitalist conceptions. Considering England as an embodiment of capitalist "civilization", Sombart made the boundary between the German and the English people in the form of antitheses. Sombart confronted the German culture, conservatism, social state and organic community to the Eniglish materialistic civilization, liberalism, capitalism and class society, interpreting the war primarily as a "battle for world-views", between the English "merchant" and the German "heroic" spirit. In this way, he gave significant contribution on the shaping of the "ideas of 1914" – the specific conservative ideology of German intellectuals, by which they legitimized the German Reich’s policy during the war years.